Forensic Stylistic Analysis of UNNES Student’s Suicide Note - Onggatta, Reggina; Maulida, Dini Eka; Andira, Missy Ayu; Balqis, Shafiah; Hamzah, Syifa Fitri; Rangkuti, Rahmadsyah (Edu-Ling: Journal of English Education and Linguistics, 2024)
Suicide notes are powerful pieces of evidence in suicide cases that left by individuals who commit suicide or who intend to commit suicide as messages, with the purpose is to voicing the victims’ feelings that remain unknown by people when they are alive. This study investigates the linguistic features contained in the suicide notes written by UNNES students by using descriptive-qualitative as the research method and applying Prokofyeva's theory of suicide notes linguistic features. The suicide note is available and can be accessed online. This study aims to analyze the forensic stylistic approach towards suicide notes by showing the characteristics of linguistic features and interpreting the messages delivered by the victims on suicide notes. The researchers classified and described the data in five distinguished characteristics of linguistic features found in the suicide note; clear reasoning, expressing emotions, text structure, grammar, and punctuation. The findings revealed that all the features are present in the suicide note, yet the researchers found that there are different tenses used in the suicide note. The results found only ellipsis in the victim’s suicide note. The data findings in this research may assist future research regarding the study of forensic stylistics, specifically in investigating suicide notes.